Colombian University Students' Experiences as Users of the English Language During International Mobility - Paula Vanessa Bello; Melba Libia Cárdenas (Universidad Nacional de Colombia, 2024)
This exploratory case study analyzes Colombian university students' experiences as English users during international mobility. Data collected through surveys and interviews were examined based on content analysis and principles of grounded theory. The students' self-perceived English proficiency and communicative performance before and during international mobility were analyzed, while challenging areas were identified. The results evidence that mobility students have insufficient levels of English proficiency to engage in academic and social activities due to inadequate production skills and a lack of practice. The students also perceive university academic English opportunities for practice as basic, and they underutilize practice spaces. Nonetheless, they highlight that active engagement in autonomous language exposure and developed interpersonal skills positively impact their perception of language performance.